Enaminone Modulators of Extrasynaptic α4β3δ γ-Aminobutyric AcidA Receptors Reverse Electrographic Status Epilepticus in the Rat After Acute Organophosphorus Poisoning - Johnstone, Timothy B. C.; McCarren, Hilary S.; Spampanato, Jay; Dudek, F. Edward; McDonough, John H.; Hogenkamp, Derk; Gee, Kelvin W. (Frontiers in Pharmacology, 2019)
ABSTRACT Seizures induced by organophosphorus nerve agent exposure become refractory to treatment with benzodiazepines because these drugs engage synaptic gamma-aminobutyric acid-A receptors (GABAARs) that rapidly internalize during status epilepticus (SE). Extrasynaptic GABAARs, such as those containing α4β3δ subunits, are a putative pharmacological target to comprehensively manage nerve agent-induced seizures since they do not internalize during SE and are continuously available for activation. Neurosteroids related to allopregnanolone have been tested as a possible replacement for benzodiazepines because they target both synaptic and extrasynaptic GABAARs receptors. A longer effective treatment window, extended treatment efficacy, and enhanced neuroprotection represent significant advantages of neurosteroids over benzodiazepines. However, neurosteroid use is limited by poor physicochemical properties arising from the intrinsic requirement of the pregnane steroid core structure for efficacy rendering drug formulation problematic. We tested a non-steroidal enaminone GABAAR modulator that interacts with both synaptic and extrasynaptic GABAARs on a binding site distinct from neurosteroids or benzodiazepines for efficacy to control electrographic SE induced by diisopropyl fluorophosphate or soman intoxication in rats. Animals were treated with standard antidotes, and experimental therapeutic treatment was given following 1 hr (diisopropyl fluorophosphate model) or 20 min (soman model) after SE onset. We found that the enaminone 2-261 had an extended duration of seizure termination (>10 hr) in the diisopropyl fluorophosphate intoxication model in the presence or absence of midazolam (MDZ). 2-261 also moderately potentiated MDZ in the soman-induced seizure model but had limited efficacy as a stand-alone anticonvulsant treatment due to slow onset of action. 2-261 significantly reduced neuronal death in brain areas associated with either diisopropyl fluorophosphate- or soman-induced SE. 2-261 represents an alternate chemical template from neurosteroids for enhancing extrasynaptic α4β3δ GABAAR activity to reverse SE from organophosphorous intoxication.